Alopecia areata incognita of the hair line. - Chieco, P.; d’Ovidio, R. (European Journal of Pediatric Dermatology, 2014)
Case report. A 16-year-old boy was first observed because the barber had noticed a thinning of the hair in the nuchal region. In the family history there was psoriasis in both maternal grandparents. In the personal history there was an ureteral replanting intervention due to bladder reflux at the age of 1 year. The physical examination showed at the hairline in the nuchal (Fig. 1) and parietal (Fig. 2) region a strip of about 1 cm with much thinner, apparently more sparse hair. There was also on the left cheek a small patch of alopecia areata (Fig. 2). The dermoscopic observation showed yellow dots and thin hair regrowth. The trichogram on not affected areas showed 90% of hairs in the anagen and 10% in telogen; on perilesional skin the hairs in the anagen phase were 95% and those in telogen 5%; the pull test, which was negative in the affected area, showed 100% of telogen hairs (Fig. 3). These data led to the diagnosis of alopecia areata incognita of the hairline.